Why interracial police-civilian interpersonal interactions can go poorly: police officer stereotype threat - Burke, Kelly C. (Psychology, crime & law, 2023)
Racially charged incidents between the police and Black civilians have sparked massive protests over racial disparities in policing. This has led many to stereotype police officers as racists, and officers themselves are aware of this. By integrating and extending prior theoretical models, this paper proposes a novel theoretical model of the various paths through which the activation of stereotype threat – officers’ fear of confirming the ‘racist police officer’ stereotype – can influence when and why White police officers display negative interpersonal behavior during routine encounters with Black civilians. The model theorizes that the activation of stereotype threat, coupled with the contextual anxiety inherent in police encounters, heightens officers’ anxiety and self-regulatory effort, leading to cognitive depletion and regulatory failure. This results in decreased empathy, ultimately ending with officers confirming the racist police officer stereotype. The paper reviews social psychological and criminal justice literature to support this theory and discusses the theoretical, practical, and research implications.